How can stakeholders influence management’s commitment to sustainable development of a company? - Bilciurescu, Andreea (2021)
Sustainability is a concept which is gaining more and more attention. The translation of sustainable development in the business context is done through Corporate Social Responsibility (CSR). CSR is widely studied in the context of corporations and large companies, but there is a lack of research in the world of Smaller and Medium Size Enterprises (SMEs), which function differently than the large ones. In this case study, a car company from Romania is chosen for studying the introduction for the first time of CSR in the business strategies. The purpose of the research is to analyse if stakeholders’ perspective on sustainability could have an influence on the management’s commitment to sustainability. Materiality analysis, a tool which is used to understand which topics are material for a company, is used to describe the stakeholders’ and the managers’ perspective on sustainability. The case study is mainly qualitative, but some quantitative research methods have also been used, allowing for facilitation and data triangulation. The answer to the research question is revealed through interviews and the observations made along the research period. The findings of the research support the idea that sustainable development is a concept which requires for systems thinking and a change of paradigm, making education one of the most important arenas for future progress. Further, findings of this study are also in agreement with conclusions from other studies on SMEs that much more research should be carried out in the context of CSR in SMEs.